Ethnomedicinal Plants of Ghorahi Sub Metropolitan City and their Adjoining Area, Dang, District - Mishra, Ghyandev (Haimaprabha, 2022)
Ghorahi is situated in the Lumbini Province Mid-Western part of Nepal. The present study was under taken Ghorahi sub-metropolitan city of Dang district indigenous knowledge on plant utilization as natural remedy and documentation of ethnomedical plant. The traditional healers, elder men and teachers were consulted as key information for the documentation of indigenous knowledge on the medicinal plants. The study was accompanied by field visits during this season. The information was taken based on local people’s knowledge. The present study has documented 34 species belongs to 23 families and 31 genera of highly utilized medicinal plants from that area used by local communities. The documentation is based on primary data collected in the field applying PRA, RRA techniques and informal interview followed by collection of plant specimen. These plants were used for the treatment of various ailments. It has been evident from the study most of the tribal group depends upon forest for firewood, fodder, holy applicants (making plates, tapari etc.). It is observed that forest is under heavy interference and its ecosystem have been change rapidly due to forest fire, lopping, grazing, fuel-wood collection etc. Therefore, indicating urgent need for conservation of these resources and indigenous knowledge about medicinal plants.